Genome-Wide Profiling of WRKY Genes Involved in Benzylisoquinoline Alkaloid Biosynthesis in California Poppy (Eschscholzia californica) - Yamada, Yasuyuki; Nishida, Shohei; Shitan, Nobukazu; Sato, Fumihiko (Frontiers in Plant Science, 2021)
Transcription factors of the WRKY family play pivotal roles in plant defense responses, including the biosynthesis of specialized metabolites. Based on the previous findings of WRKY proteins regulating benzylisoquinoline alkaloid (BIA) biosynthesis, such as CjWRKY1—a regulator of berberine biosynthesis in Coptis japonica—and PsWRKY1—a regulator of morphine biosynthesis in Papaver somniferum—we performed genome-wide characterization the WRKY gene family in Eschscholzia californica (California poppy), which produces various BIAs. Fifty WRKY genes were identified by homology search and classified into three groups based on phylogenetic, gene structure, and conserved motif analyses. RNA sequencing showed that several EcWRKY genes transiently responded to methyl jasmonate, a known alkaloid inducer, and the expression patterns of these EcWRKY genes were rather similar to those of BIA biosynthetic enzyme genes. Furthermore, tissue expression profiling suggested the involvement of a few subgroup IIc EcWRKYs in the regulation of BIA biosynthesis. Transactivation analysis using luciferase reporter genes harboring the promoters of biosynthetic enzyme genes indicated little activity of subgroup IIc EcWRKYs, suggesting that the transcriptional network of BIA biosynthesis constitutes multiple members. Finally, we investigated the coexpression patterns of EcWRKYs with some transporter genes and discussed the diversified functions of WRKY genes based on a previous finding that CjWRKY1 overexpression in California poppy cells enhanced BIA secretion into the medium.